Funkcionalʹno-stilevaâ specifika folʹklornogo teksta v acpekte èkstralingvističeskoj obuslovlennosti - Vengranovič, Marina A. (Stylistyka, 2021)
The article considers the problem of defining the stylistic peculiarities of the folklore text. As criteria for objective investigation of the problem the author suggests using the functional approach, presupposing the study of any kind oftext in two inseparable aspects - textual and extralinguistic. In accordance with this approach the author distinguishes the following basie extralinguistic factors revealed in the folklore text: folklore thinking, character of the folklore communication and collective authorship, which together determine specific character of the folklore communicative act participants - speech subject and addressee. The author focuses on the predominating features of the folklore thinking, which deterrnine the unity of the generalizing method in folklore w ithin which complex semantic structure of the folklore word is organized as well as a specific type of depiction - literary-generalizing. Influence of the folklore communication is perfom1ed in natura! ways and can be characterized by continuity and synchronizing the acts of performance and perception; heterogenie character, activity of both participants. The consequences of it are examined by the author as literary syncretism of the folklore text, the evidence of the autorcommunicational text features, hypertext structure as well as peculiarities of realizing the phenomena of subject and address. Analyzing extralinguistic factors the author comes to conclusion of granting the folklore speech the status of stylistic variety of literary speech with its own specific features.